2023
DOI: 10.3389/fphar.2023.1124607
|View full text |Cite
|
Sign up to set email alerts
|

Immune-enhancing activity of polysaccharides and flavonoids derived from Phellinus igniarius YASH1

Abstract: Introduction:Phellinus igniarius (P. igniarius) (Sanghuang) is a widely used traditional Chinese medicine fungus, and its natural products have great potential for clinical application in immune enhancement. This study aimed to explore the immune-enhancing activity and underlying mechanisms of the polysaccharides and flavonoids derived from Phellinus igniarius (P. igniarius) and to provide a theoretical and experimental basis for the development of novel drugs.Methods: Wild P. igniarius YASH1 from the Loess Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Lu et al found through animal experiments that the mycelia of Antrodia camphorata and Armillariella tabescens have protective effects on the liver [ 17 ]. There are many active components in the MPI, which have many functions, such as anti-oxidation, anti-tumor, and immune regulation, but the cost of extracting these components is high [ 18 , 19 ]. In this study, MPI was used directly to treat colitis, and CB and MPI were used in combination.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al found through animal experiments that the mycelia of Antrodia camphorata and Armillariella tabescens have protective effects on the liver [ 17 ]. There are many active components in the MPI, which have many functions, such as anti-oxidation, anti-tumor, and immune regulation, but the cost of extracting these components is high [ 18 , 19 ]. In this study, MPI was used directly to treat colitis, and CB and MPI were used in combination.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the important active ingredients of Sanghuangporus alpinus [9]. According to research, the Sanghuangporus exopolysaccharide exhibits various activities, such as anticancer [10], blood sugar-lowering [11], antioxidant [12], immunity-boosting [13] properties, and has broad research prospects. Studies have shown that exopolysaccharides fight cancer by increasing immune cell activity and apoptosis [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular polysaccharides are mainly derived from fermentation broth [6][7][8][9]. The extracellular polysaccharides of S. sanghuang are widely-studied as bioactive compounds and show a broad range of pharmacological activities, including anticancer [10], hypoglycemic [11], antioxidant [12], and immunity-enhancing [13] properties. Liu et al [14] found that Phellinus baumii polysaccharide can promote the proliferation of RAW264.7 cells, enhance their phagocytic ability, promote their secretion of IL-6 and TNF-α cytokines, and have immunomodulatory activity.…”
Section: Introductionmentioning
confidence: 99%